Obsessive–Compulsive Personality Symptoms Predict Poorer Response to Gamma Ventral Capsulotomy for Intractable OCD - Copetti, Maria Eugênia; Lopes, Antonio C.; Requena, Guaraci; Johnson, Isaac N. S.; Greenberg, Benjamin D.; Noren, Georg; McLaughlin, Nicole C. R.; Shavitt, Roseli G.; Miguel, Eurípedes C.; Batistuzzo, Marcelo C.; Hoexter, Marcelo Q. (Frontiers in Psychiatry, 2020)
The Gamma ventral capsulotomy (GVC), a radiosurgical procedure which aims to create lesions in the ventral part of the anterior limb of the internal capsule (ALIC), has been used as a treatment option for intractable obsessive-compulsive disorder (OCD) patients who did not respond to several first-line treatments attempts. However, changes in personality disorder symptoms after GVC were not investigated. The aims of this study were to investigate changes in personality disorder symptoms after GVC and to search for baseline personality disorder symptoms predictors of clinical response. Fourteen treatment-intractable OCD patients who underwent GVC completed the Structured Clinical Interview for DSM-IV Personality Disorders (SCID-II) at baseline and one year after the procedure. Wilcoxon signed-rank test was performed to investigate personality disorder symptom changes before and after surgery. Linear regression models were tested for predicting treatment response using baseline personality disorder symptoms as independent variables. We did not observe any quantitative changes in personality disorder symptoms after GVC. The higher the severity of obsessive-compulsive personality disorder symptoms at baseline, the worse was the treatment response after GVC for OCD (β= -0.085, t-value= -2.52, p-value= 0.027). These findings advocate for the safety of the GVC procedure in this specific population of intractable OCD patients in terms of personality disorder symptom changes. It also highlights the importance of taking into account the severity of obsessive-compulsive personality disorder symptoms when GVC is indicated for intractable OCD patients.